When Teratology and Augmented Reality Entwine: A Qualitative Phenomenological Analysis in a Museal Setting - Lucas L. Boer; Frédérique Schol; Colin Christiaans; Jacobus Duits; Thomas Maal; Dylan Henssen (Sensors)
Background: The Museum for Anatomy and Pathology at the Radboud University (The Netherlands) has created a permanent teratological exhibition, which is enhanced with augmented reality (AR) modalities. This exhibition serves various (post)graduate educational purposes and is open to the general public. However, data on visitors’ views and experiences regarding the teratological collection and AR models are currently lacking. Methods: To address this, a qualitative study was conducted to explore visitors’ opinions and experiences. One-on-one in-depth interviews were conducted using a predefined topic list, with audio recordings transcribed verbatim. Thematic analysis was applied to the twenty-six interview transcripts. Results: The findings indicate that publicly displaying teratological specimens alongside AR modalities is valued and positively received by both (bio)medical students and laypeople alike. AR enhances understanding of dysmorphology and provides a more interactive and engaging learning experience for complex topics. Conclusion: The use of AR within a teratological exposition holds tremendous educational potential and improves public awareness and acceptance of developmental anomalies. Moreover, it provides a unique opportunity to reflect on both historical and contemporary bioethical issues.